An analysis of smartphone overuse recognition in terms of emotions using brainwaves and deep learning - Kim, Seul-Kee; Kang, Hang-Bong (Neurocomputing (Amsterdam), 2018)
•The smartphone addiction risk group (13 subjects) and non-risk group (12 subjects) watched videos portraying the concepts of relaxed, fear, joy, and sadness.•The risk group was more emotionally unstable than the non-risk group in EEG. Especially, in recognizing fear, a clear difference appeared between the risk and non-risk group.•We assessed the asymmetry power with respect to theta, alpha, beta, gamma, and total activity in 11 lobes, and the gamma band was the most obviously different between the risk and non-risk groups.•We found that the measurements of activity in the frontal, parietal, and temporal lobes were indicators of emotion recognition.•Through the deep belief network, we confirmed that the risk group had higher accuracy in low valence and arousal; on the other hand, the non-risk group had higher accuracy in high valence and arousal. The overuse of smartphones is increasingly becoming a social problem. In this paper, we analyze smartphone overuse levels, according to emotion, by examining brainwaves and deep learning. We assessed the asymmetry power with respect to theta, alpha, beta, gamma, and total brainwave activity in 11 lobes. The deep belief network (DBN) was used as the deep learning method, along with k-nearest neighbor (kNN) and a support vector machine (SVM), to determine the smartphone addiction level. The risk group (13 subjects) and non-risk group (12 subjects) watched videos portraying the following concepts: relaxed, fear, joy, and sadness. We found that the risk group was more emotionally unstable than the non-risk group. In recognizing Fear, a clear difference appeared between the risk and non-risk group. The results showed that the gamma band was the most obviously different between the risk and non-risk groups. Moreover, we demonstrated that the measurements of activity in the frontal, parietal, and temporal lobes were indicators of emotion recognition. Through the DBN, we confirmed that these measurements were more accurate in the non-risk group than they were in the risk group. The risk group had higher accuracy in low valence and arousal; on the other hand, the non-risk group had higher accuracy in high valence and arousal.